Monitorización y Predicción del consumo energético en O-RAN - Álvarez-Merino, Carlos Simón; Luo Chen, Hao Qiang; Pinola, Jarno; Khatib, Emil Jatib; Barco-Moreno, Raquel (My University, 2025)
Energy efficiency has emerged as a cornerstone in the development of b5G/6G networks, particularly within the framework of Open Radio Access Networks (O-RAN). This paper presents a monitoring and prediction system designed to reduce the energy consumption of critical O-RAN components, namely the Central Unit (O-CU) and Distributed Unit (O-DU). The proposed approach leverages the MAPIE algorithm to generate robust energy consumption forecasts with theoretically grounded prediction intervals, allowing for real-time network resource optimization without compromising service quality. Experimental validation was conducted in a disaggregated commercial O-RAN environment, emulating realistic operational conditions, supporting the identification of consumption patterns and enabling proactive network management. The proposed system serves as a foundation for intelligent, energy-aware management strategies in future mobile networks, paving the way for automated decision-making in Service Management and Orchestration (SMO) systems.
Keywords: Sistemas de comunicación inalámbricos; Ahorro de energía; Eficiencia energética; b5G; 6G; Predicción; Monitorización; Arquitectura de red